Inka Human Sacrifice and Mountain Worship : Strategies for Empire Unification - Besom, Thomas, 1960- (Book collections on Project MUSE., 2013)
In this study, the author explores the ritual practices of human sacrifice and the worship of mountains, attested in both archaeological investigations and ethnohistorical sources, as tools in the establishment and preservation of political power within the Inka empire. -- Provided by publisher.